Cultural Taboos and Misinformation about Menstrual Health Management in Rural Bangladesh - Silvia Castro; Kristina Czura (CESifo GmbH, 2024)
Every month, millions of women worldwide face challenges managing their menstrual hygiene, suffering negative impacts on their health, education, and productivity. Cultural taboos and social norms may contribute to harmful health behaviors and may also interfere with attempts to improve knowledge. Our study explores how deep-rooted cultural norms relate to, and potentially hinder, effective menstrual hygiene practices. We engaged with women in rural communities in Bangladesh to understand and quantify their well-being during menstruation and their perceptions on the prevailing social norms around menstrual health. With an educational intervention, we aim to disseminate crucial knowledge on menstrual hygiene practices. Our findings show that while the information intervention succeeded in reshaping certain misconceptions and menstrual practices, it was not enough to alter deep-seated norms regarding the washing and maintenance of menstrual cloth.
Keywords: I12; I15; D91; O12; 330; social norms; menstrual health management; menstrual hygiene; information; adverse health behavior